Digital Transformation And Business Model Innovation: Examining The Impact Of Digital Technologies On Sme Competitiveness - Daniel Pangaribuan; Riris Hutapea; Ezra Reni Silva Situmorang; Andre M.P Sianturi (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
Digital transformation has become a crucial factor in enhancing organizational competitiveness in the digital economy. The rapid development of technologies such as artificial intelligence (AI), big data analytics, cloud computing, and the Internet of Things (IoT) has significantly changed how firms create, deliver, and capture value in business activities. This study aims to examine the relationship between digital transformation, business model innovation, and the competitiveness of small and medium-sized enterprises (SMEs) through a literature review approach. The study employs a qualitative literature review method by analyzing relevant academic publications from 2020 to 2024. The literature sources were collected from reputable journals and academic databases such as Scopus and Google Scholar. The findings indicate that digital transformation acts as a key driver of business model innovation by enhancing digital capabilities, integrating data-driven processes, and utilizing digital platforms in business operations. These innovations enable SMEs to improve operational efficiency, expand market access, and create new value propositions for customers. However, SMEs still face several challenges in implementing digital transformation, including limited digital literacy, financial constraints, and inadequate technological infrastructure. Therefore, supportive policies, digital capacity development, and collaboration among governments, private sectors, and educational institutions are essential to accelerate sustainable digital transformation among SMEs.